Types of Impoliteness Discovered in "Karen's Dinner" Australia - Sonia Rahman; Mhd. Johan (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2023)
In this study, some forms of abusive behavior in Australia are analyzed through the lens of a pragmatic study based on "Karen's Dinner." The purpose of this study was to find out the various forms of rude behavior depicted in the Australian version of "Karen's Dinner" and how this behavior is commonly used. Speakers and listeners at the restaurant known as "Karen's Dinner" in Australia eventually became the source of the data collected there. Researchers use a study strategy that includes both descriptive and qualitative analysis so that they can offer the results of their investigations. Bousfield (2008) is a source of research designs used by researchers. The observation method described by Sudaryanto (2015) Â was used by researchers to collect data. The researcher is responsible for carrying out the procedures involved in data collection, which begins with the researcher watching videos on YouTube and examining the settings to be evaluated. Third, the researcher finally succeeded in identifying various types of impoliteness that can be found among utterances that already contain various types of impoliteness. In the Australian restaurant known as "Karen's Dinner," both speakers and listeners engage in the use of speech that contains various forms of impoliteness. This includes affective impoliteness, coercive impoliteness, and entertaining impoliteness.